2022
DOI: 10.1186/s12939-022-01783-5
|View full text |Cite
|
Sign up to set email alerts
|

‘HIV ended up in second place’ − prioritizing social integration in the shadow of social exclusion: an interview study with migrants living with HIV in Sweden

Abstract: Background Migrants are overrepresented among people living with HIV in Sweden as they often face conditions that increased their risk and vulnerability for HIV/STI infections prior, during or after migration. Yet, there is limited research on their experiences and perceptions of living with HIV in the Swedish context. This study aims to explore migrants’ experiences of living with HIV in Sweden. Methods This is a qualitative study based on in-dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Lack of health insurance coverage and prohibitive costs have been identified as major barriers to urgent HIV care postresettlement [58]. Inadequate basic needs (housing, employment) may lead MIDP to prioritise other needs over sexual health [17,36,59]. Furthermore, inadequate health system navigation support and insensitive provider interactions may affect how those precarious immigration status accessed sexual health care [60].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of health insurance coverage and prohibitive costs have been identified as major barriers to urgent HIV care postresettlement [58]. Inadequate basic needs (housing, employment) may lead MIDP to prioritise other needs over sexual health [17,36,59]. Furthermore, inadequate health system navigation support and insensitive provider interactions may affect how those precarious immigration status accessed sexual health care [60].…”
Section: Resultsmentioning
confidence: 99%
“…Many of the challenges that migrant people face relate to social determinants of health, including poverty and cultural and language barriers, rather than HIV/STI status itself. Therefore, larger investment in community support groups, peer-educators and interpreters will not only improve may improve HIV/STI and other sexual health disparities [59,86]. Developing supportive environments through peer-led advocacy and provider sensitivity training could help produce long-term, sustainable improvements to sexual health while at the same time, enhance sex equity [88–90].…”
Section: Discussionmentioning
confidence: 99%
“…Sweden may be attractive to LGBTQI + migrants fleeing persecution in their home countries as they can be granted protection according to Swedish law. A qualitative study involving LGBTQI + migrants living with HIV in Sweden suggested that current legislation in Sweden makes it a safe and secure country where LGBTQI people can live a normal life and access HIV treatment without discrimination [ 13 ]. Previous research has also shown that self-perceived discrimination is related to gender, ethnic origin and religion [ 12 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Discrimination against migrants can take place for different reasons and in different settings, including schools, labour markets, workplaces, public and health care services [ 12 , 13 , 16 ]. According to Schutze et al, preconceived notions about migrants can affect the welfare services that they receive in Sweden [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a major global public health issue, approximately 38.4 million people worldwide were living with HIV (human immunodeficiency virus) at the end of 2021, and a significant number of new infections are reported each year (1.5 million globally in 2021) [ 1 ]. Migration has been proved as a potential risk factor for this significant rise in new HIV infections because of biological, socio-economic, and structural factors [ 2 5 ]. For example, evidence from the USA, Russia, and the Netherlands all reported that migrants were vulnerable to HIV infection with sexual risk behaviors and tended to become the “bridge population” between destination country and home country [ 6 11 ].…”
Section: Introductionmentioning
confidence: 99%